#TITLE_ALTERNATIVE# - ARMUNDITO (NIM : 25399014); Pembimbing: Ir.Suprihanto Notodarmojo, Ph.D. , ERIK
Flow through porous medium can be used as flocculator. It is assumed that the tortuosity of the flow will enhance the chance for agglomeration of destabilized particle to form settleable flocs. The media used in this laboratory scale experiment were marble (w = 1,5 cm), gravel I (average ( = 2,25 cm), gravel II (average 4) = 1,5 cm) and gravel III (average ( = 1,05 cm). The tortuosity factors (co) used in the experiment were col = 0,67, w2 = 0,65, w3 = 0,63 and w = 0,60. The results, in general, give good performances for all series experience in the first 3 meter of distance. Results show that for the artificial raw water, turbidity removal efficiencies up to 99% or higher were achieved. The value of G observed were in the range of 18 to 36 s- while the value Gtd in the range of 667 to 25008. The Reynolds numbers in the range of 102,30 to 419,93, then the flow through this porous medium is turbulent. Evaluation on the hydraulic performance of the reactor shows that the effect of short circuit phenomenon was more significant than the dead pore phenomenon. It is indicated by the comparation between the actual and theoretical detention times. The actual detention times were longer than the theoretical ones. In the range of co used in this experiment statistically has no significant effect to the removal of turbidity, although increasing in the co values show a better performance of the reactor. Since the dispersion factors in the range of 0 to 8,3 then the reactor is a plug flow reactor. For natural raw water, the flocculation also shows good performances in the removal of turbidity, organic matter and total suspended solids.